PENINGKATAN DAYA SAING PRODUK ANYAMAN DAUN MANSIANG TARATAK MELALUI VARIASI DAN KUALITAS PRODUK DI KABUPATEN LIMA PULUH KOTA - Ratni Prima Lita; Rahmi Fahmy; Meuthia Meuthia (Jurnal Hilirisasi IPTEKS, 2023)
Mansiang weaving is a famous handicraft in Jorong Taratak, which has been passed down from generation to generation and has become an ancestral heritage. The craft business aims to develop variations of woven Taratak mansiang leaf products and to improve the quality of woven Taratak mansiang leaf products. The activity methods carried out are training, practice, discussion, and business consultation methods involving craftsmen groups in Taratak. The training participants are group leaders consisting of 6 people. Before the training is carried out, a pre-test is conducted to determine the participants’ abilities, and after the training, a post-test is carried out to determine the participants’ ability to absorb the material presented. The results of the activities increase craftsmen’s understanding of market opportunities in the middle and upper segments, develop product variations that are in demand by the middle and upper segments, and improve product quality to target the middle and upper segments. From the results of the activity, 90% of the craftsmen understood the material presented. There are six product designs that will be planned for production. There are 2 to 5 products whose production results we evaluate, which in turn can be improved in the future. From the activities, service activities are expected to be sustainable, hence they can have an impact on partner business performance. It is necessary to develop product variety and quality by adding production equipment such as sewing machines and special training for production.